-7=4c+7c-2c

Simple and best practice solution for -7=4c+7c-2c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7=4c+7c-2c equation:


Simplifying
-7 = 4c + 7c + -2c

Combine like terms: 4c + 7c = 11c
-7 = 11c + -2c

Combine like terms: 11c + -2c = 9c
-7 = 9c

Solving
-7 = 9c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-9c' to each side of the equation.
-7 + -9c = 9c + -9c

Combine like terms: 9c + -9c = 0
-7 + -9c = 0

Add '7' to each side of the equation.
-7 + 7 + -9c = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -9c = 0 + 7
-9c = 0 + 7

Combine like terms: 0 + 7 = 7
-9c = 7

Divide each side by '-9'.
c = -0.7777777778

Simplifying
c = -0.7777777778

See similar equations:

| y=4-34 | | 3x^2+8x-4=0 | | x*x-x-2=0 | | 4y+7= | | -x*x-14x-50=0 | | 12+36=13y-17y | | 5h+13=13 | | 4x-34=345 | | 7p-2p-p= | | 40=8-16k | | x*x+5x+6=0 | | -3x^2-8x+4=0 | | -3x-8x+4=0 | | 7x*x-54x+35=0 | | 5x-3x+6=56 | | 30=5x+5 | | 8x=-17 | | 29x=0 | | x*x-2x-3=0 | | 5x-3x=4+10 | | x*x+7x+6=0 | | 2x+3x+5x=20 | | 3(3x+6)=3(x+8) | | -x*x-6x-5=0 | | 12+5(9-7X)=9-11X | | x^2+25x+196=0 | | 4+e=4 | | 2p+32=14p | | 2n+34=14p | | x+-2=5 | | -3+m=-13 | | 5x+3y+4z=7 |

Equations solver categories